Influence of inorganic flame retardants, chemisorbed on polyester fiber materials on the patterns of it thermal destruction - Reva, Ольга; Bogdanova, Валентина; Nazarovich, Андрей; Shukelo, Зоя (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
The authors investigated the dependence of the thermo-oxidative degradation regularities the composite nano-layered system, based on polyester fiber material with chemically grafted to it inorganic flame retardants, from the chemical composition and particle size distribution in the burning protection mixture.